PHENOTYPIC DIVERSITY OF SOME OLIVE TREE PROGENIES ISSUED FROM A TUNISIAN BREEDING PROGRAM - Laaribi Ibtissem; Mezghani Aiachi Mouna; Mars Messaoud (European Scientific Journal, ESJ, 2014)
This work was done to quantify and to evaluate the distribution of the genetic diversity observed within and between olive tree seedlings issued from a Tunisian breeding program. Forty-eight ‘Chemlali’ olive tree seedlings which were issued from free-, self-, and cross pollination of cultivar ‘Chemlali’ with ‘Coratina’ were characterized by combining 17 quantitative and 32 qualitative traits. Principal component analysis was used for the identification of the pattern of morphological variation. Variance analysis revealed significant differences between progenies. Variation coefficients ranged from 8.36 to 32.93% for ‘Chemlali’ ×’Coratina’ descendants, from 7.93 to 80.91% for ‘Chemlali’ free pollination descendants and from 10.38 to 74.88% for ‘Chemlali’ self pollination descendants. Shannon and Nei indices indicated also the variation between descendants within crossings. However, some seedlings showed tree, leaf, fruit and endocarp shapes and sizes which differs from the typical of ‘Chemlali’ cultivar. An increase of the fruit size and an improvement of the flesh to stone ratio were noted; thus the first three principal components explained 72% of the total observed variability. PC1 was mainly correlated to fruit and endocarp sizes and flesh to stone ratio; and PC2 was mainly correlated to fruit and endocarp shapes. Descendants’clustering was done according to the main discriminant parameter which is the fruit size. Most ‘Chemlali’ × ‘Coratina’ descendants were closely clustered. ‘Chemlali’ free and self pollination descendants were not closely grouped, but shows clear overlapping data, which suggests that these two types of pollination can induce a comparative morphological variability.